Ekspresi Level Gen mRNA Protein Ekstraseluler Otak Embrio Mencit Black-6 UK-12 Akibat Induksi 2-Methoxyethanol : Analisis secara Real Time RT-PCR - Yulia Irnidayanti; Win Darmanto; Agus Abadi (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2010)
The aim of this research was to investigate impact of 2-methoxyethanol, a major industrial chemical, and its individual metabolites on the expression DNA of the embryonic brain development of black-6 mice. The expression levels mRNA protein of GAPDH, Fibronectin, tenascin, vimentin, Neurofilamen, NCam between brain embrio treatment with 2-ME at gestation day 12 and Embryo control were achieved. The Electroforesis DNA on brain Embryonic day 12 showed that there were expression of GAPDH (447bp), Fibronectin (462bp), NCAM (293 bp), Tenascin (416bp), Vimentin (327), Neurofilamen high (301bp), Neurofilamen medium (289bp), Neurofilamen low (398bp). This Data not showed. The expression of level of mRNA for protein Vimentin at embryonic brain treatment at GD-12 is 487 copies, meanwhile on the embryonic brain control is 209 copies. This expression is tendency very higher than control. Another level of mRNA for protein fibronectin, NCAM, Tenascin, Neurofilament were tendency not difference between embryonic brain treatments and control. Intermediate filaments, vimentin, is found in specific cell types in the developing and adult central nervous systems (CNS), particularly astrocytes. Recently, found that vimentin immunoreactivities were increased in astrocytes and/or macrophages in the spinal cords of rats with autoimmune inflammation). So that The higher level mRNA for protein vimentin caused by effect 2-methoxyethanol. Vimentin contribute to the repair of brain through the migration of activated cells and increased level vimentin at embryionic brain treatment with 2-ME.